Professional satisfaction of masters of nursing versus Abraham Maslow’s hierarchy of needs — analysis of answers to open-ended questions - Brayer, Aneta; Marcinowicz, Ludmiła (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. Professional satisfaction of nurses is the subject of many studies, but little is known about the professional satisfaction of masters of nursing. Aim of the study. The aim of the study was to determine the reasons for satisfaction or dissatisfaction among masters of nursing on the basis of open-ended questions, as well as to utilize the assumptions of A. Maslow’s hierarchy of needs in the attempt to explain the results in that field. Material and methods. A survey was conducted among 272 masters of nursing employed at various health care facilities in central and north-eastern Poland. The study tool was a standardized questionnaire supplemented with two open-ended questions referring to the reasons for professional satisfaction or dissatisfaction. The analysis of the respondents’ free answers to the open-ended questions is the subject of this work. Results. The respondents’ answers were divided into 663 units, including 298 (45%) referring to satisfaction, and 365 (55%) referring to dissatisfaction. Then the units were grouped into categories corresponding to particular types of needs according to Maslow’s hierarchy of needs. Conclusions. The greatest source of satisfaction among masters of nursing is the factors concerning interpersonal relations at work, which is connected with the need of belonging. The main reason for dissatisfaction is the economic aspect, namely the level of compensation and relaxation time, which may result in failure to satisfy certain biological needs. Nursing Topics 2014; 22 (1): 12–19